Therapeutic potential of atorvastatin in ischemic stroke: an investigation into its anti-inflammatory effect by targeting the gut-brain axis - Liuzhu Chen; Linpei Zhuo; Jie Zheng; Xiaoyun Sun; Jing Sun; Jiaming Liu (Journal of Translational Medicine)
Abstract Background Recent studies have highlighted the vital role of gut microbiota in the pathogenesis of Ischemic stroke (IS). However, the effects and underlying mechanisms of atorvastatin on IS via regulating gut-brain axis remain unclear. Thus, this study aimed to explore the relationship between atorvastatin, gut microbiota and IS through animal experiments, clinical trials and Mendelian randomization (MR) analysis. Methods Male mice were induced with bilateral common carotid artery occlusion (BCCAO) to establish an IS animal model, and then intragastrically treated with atorvastatin. Neurological deficits, microglia activation, and the levels of NLRP3 inflammasome and NF-κB pathway-related proteins were detected. Meanwhile, gut microbiota composition and intestinal barrier integrity were evaluated. In this prospective study, we recruited IS patients undergoing atorvastatin treatment, evaluated their functional outcomes, collected fecal samples, and assessed gut microbiota functions. Moreover, the causal relationships between specific bacteria, inflammation and IS were assessed via MR analysis. Results Our results showed that atorvastatin treatment significantly improved neurobehavioral deficits, suppressed activation of microglia, and inhibited NF-κB pathway as well as the formation of the NLRP3 inflammasome, reduced the release of inflammatory cytokines, including IL-1β and IL-18, which were reversed by antibiotics treatment. We further identified an increase in the genus Lachnospiraceae NK4A136 in atorvastatin-treated mice. Subsequent clinical experiments were conducted to explore the effects by analyzing the characteristic bacteria, such as Ruminococcus torques and Lachnospiraceae NK4A136. The higher abundances of Ruminococcus torques and Lachnospiraceae NK4A136 were associated with a good outcome in atorvastatin-treated IS patients. MR analysis further revealed that these microbes were negatively correlated with inflammatory factor levels, and showed inhibitory effects on the Akt/NF-κB/NLRP3 pathway and PLA2G7 gene expression. Conclusion These findings demonstrated the roles of atorvastatin in regulating Akt/NF-κB/NLRP3 pathway to inhibit neuroinflammation through specific bacteria, which implied a novel way for IS treatment.